2001
DOI: 10.1136/fn.84.3.f183
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of prophylactic etamsylate: follow up at 2 years of age

Abstract: Aim-To assess the role of etamsylate* in reducing the risk of haemorrhagic brain damage and its consequences. Design-Follow up of babies recruited into a randomised controlled trial. Methods-A total of 334 infants born before 33 weeks gestation in France and Greece were randomly allocated within the first four hours of birth either to receive etamsylate or to act as controls. The principal outcomes in the trial were death or impairment and/or disability at the age of 2 years. Results-Fifty nine children were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 8 publications
0
15
0
3
Order By: Relevance
“…Schmidt questioned if endpoints chosen for many neonatal randomized control trials were sensitive to detecting impact on disability outcomes. Elbourne et al [2001] evaluated the impact of ethamsylate on the prevention of IVH and subsequent death or disability on VLBW neonates Ͻ33 weeks. Neuromotor disability at age 2 years was classified as moderate if the child was unable to sit, needed help to walk, or had difficulty using his hands.…”
Section: Early Childhood Developmental Competencies At Ages 18 Monthsmentioning
confidence: 99%
“…Schmidt questioned if endpoints chosen for many neonatal randomized control trials were sensitive to detecting impact on disability outcomes. Elbourne et al [2001] evaluated the impact of ethamsylate on the prevention of IVH and subsequent death or disability on VLBW neonates Ͻ33 weeks. Neuromotor disability at age 2 years was classified as moderate if the child was unable to sit, needed help to walk, or had difficulty using his hands.…”
Section: Early Childhood Developmental Competencies At Ages 18 Monthsmentioning
confidence: 99%
“…The second trial, in which 334 premature infants received ethamsylate in the first 4 h after birth, showed no difference in incidence of IVH compared with placebo group. In both trials, long-term patient follow-up showed no benefits in neurodevelopmental outcomes and neuromotor or cognitive function (Elbourne et al, 2001;Schulte et al, 2005). Failure of indomethacin and ethamsylate to improve the IVH global outcome is probably attributable to the fact that although COX inhibition may prevent the initial increase in CBF causing IVH, it could lead to harmful neuronal effects.…”
Section: Prostacyclin Metabolism and Cerebral Intraventricular Hemmentioning
confidence: 99%
“…This is not supported by the follow up of the EC trial, in which deaths were similar in the etamsylate and placebo groups. 16 The EC trial also failed to detect any long term benefit of etamsylate treatment, but did not report on the incidence of patent ductus. They did not find a reduction in the number of squints.…”
Section: Discussionmentioning
confidence: 99%